THE GOVERNMENT REGULATION OF TOURISM IN ТНЕ PRC - Ткачук, Леоніла (Human Geography Journal, 2014)
Basic directions of national tourism policy of the People’s Republic of China are examined in the article. Principles of state regulation of tourism in the People’s Republic of China are considered. The forming pre-conditions, legislative and institutional bases and mechanisms of realization of national strategy of creation in the People’s Republic of China high-efficiency industry of tourism and leisure are analysed. Actual trends of state regulation of the tourism industry in the medium term are revealed.